Representasi Budaya Jember dalam Jember Fashion Carnival: Pendekatan Teori Representasi Stuart Hall - Ivana Grace Sofia Radja; Leo Riski Sunjaya (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This article aims to analyze the representation of Jember culture in the Jember Fashion Carnival (JFC) using Stuart Hall's representation theory approach. The main concepts applied in this analysis are change and resistance, which are used to understand how cultural symbols are represented and interpreted in JFC. The data collection process was carried out through literature study. Where the data obtained comes from the results of research and scientific work of other people which is studied and then developed. Data analysis was carried out by combining the concepts of Stuart Hall's representation theory with the findings found in the JFC event. The results of the literature study analysis show that JFC is an important forum for representing Jember's cultural identity through costume modifications, dance, music and other performances. In addition, the media plays an important role in the spread and influence of these cultural representations. In the context of Stuart Hall's representation theory, change refers to the transformation of cultural symbols in the JFC, while resistance describes the process of building cultural representations through interactions and agreements between JFC actors, the government and society. Through this process, Jember's cultural identity is represented and interpreted in JFC events. The implication of the results of this research is the need for continuous support in developing and promoting Jember culture through collaborative efforts between the government, cultural actors and the community. In this case, JFC can be an effective means of strengthening and expanding understanding and appreciation of Jember's cultural identity.